2020
DOI: 10.1016/j.heliyon.2020.e03718
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable films based on purple yam starch/chitosan for food application

Abstract: One of the most critical challenges for the food packaging industry to overcome is the development of biodegradable coatings from renewable sources. In this work, purple yam starch (PYS), chitosan (CS), and glycerol were blended to obtain biodegradable films for characterization as intended food coatings. The films had a homogeneous surface, and the amount of CS highly influenced the film thickness. Infrared spectroscopy indicated hydrogen bond interactions between PYS and CS in the films. Thermogram data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 33 publications
(50 reference statements)
3
19
1
Order By: Relevance
“…Also, well-dispersed nanofiber hinders the path for water molecule diffusion through the film due to the more compact, homogeneous polymer structures [29]. As shown in Figure 6, the WVP value of the GU/CH/20BC film is 3:7 × 10 −11 g m −1 s −1 Pa −1 (24 h), similar to that found in a previous study on the improvement of the shelf life of yam starch/chitosan-coated apples [36]. Therefore, this film has a good potential for the shelf life of various food types.…”
Section: Transparencysupporting
confidence: 84%
“…Also, well-dispersed nanofiber hinders the path for water molecule diffusion through the film due to the more compact, homogeneous polymer structures [29]. As shown in Figure 6, the WVP value of the GU/CH/20BC film is 3:7 × 10 −11 g m −1 s −1 Pa −1 (24 h), similar to that found in a previous study on the improvement of the shelf life of yam starch/chitosan-coated apples [36]. Therefore, this film has a good potential for the shelf life of various food types.…”
Section: Transparencysupporting
confidence: 84%
“…As shown in Figure 3, KGCL film exhibited a good microstructure in its cross-sectional surface, which may be related to the uniform dispersion of chitosan and KGM matrix and their good miscibility and compatibility, resulting in strong interaction and adhesion at the interface between chitosan and KGM [9]. The homogenous surface of CSCL film might be due to the complete dissolution of the starch and chitosan in its film-forming solution [50]. Therefore, as a packaging material for Mongolian cheese, KGCL and CSCL films possessed a better microstructure.…”
Section: Semmentioning
confidence: 97%
“…Kargarzadeh et al [ 17 ] reinforced rice husk fiber into starch biocomposite films and Yang et al [ 18 ] prepared wheat straw and polylactic acid biocomposite. To the best of the authors’ knowledge, research on active SPS films is relatively scarce, while several starch films have been reported on tuberous plants including potato starch [ 19 , 20 , 21 , 22 ], tapioca starch [ 3 , 23 , 24 ], cassava starch [ 25 , 26 , 27 , 28 ] and yam [ 29 , 30 ]. In this research, the starch and peel of purple sweet potato were utilized as starch-based films with pH-sensitive indicator dye.…”
Section: Introductionmentioning
confidence: 99%